2013
DOI: 10.2215/cjn.03950412
|View full text |Cite
|
Sign up to set email alerts
|

Decreased CD5+ B Cells in Active ANCA Vasculitis and Relapse after Rituximab

Abstract: SummaryBackground and objectives B cell significance in ANCA disease pathogenesis is underscored by the finding that ANCA alone can cause disease in mouse models and by the effectiveness of rituximab as therapy in ANCA-small vessel vasculitis (ANCA-SVV). To avoid infections and adverse events from therapy, clinicians require improved markers of disease activity and impending relapse to guide immunosuppression strategies after rituximab treatment.Design, setting, participants, & measurements The B cell phenotyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
64
1
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 84 publications
(70 citation statements)
references
References 39 publications
(41 reference statements)
3
64
1
2
Order By: Relevance
“…In humans, B-lymphocyte clusters have been observed in rapidly progressive GN kidneys, similar to those described in lupus nephritis (170). Aberrations in circulating B cells have been described in patients with active disease in AAV with increased BCR signaling, altered proportions of CD51 B cells, and decreased Breg numbers or function (105)(106)(107)171). Not surprisingly, therefore, rituximab in combination with corticosteroids is an effective (and Food and Drug Administrationapproved) therapy for inducing remission in patients with AAV, but its efficacy in treating patients with advanced renal disease has not been established yet (172).…”
Section: Role In Gnmentioning
confidence: 75%
See 1 more Smart Citation
“…In humans, B-lymphocyte clusters have been observed in rapidly progressive GN kidneys, similar to those described in lupus nephritis (170). Aberrations in circulating B cells have been described in patients with active disease in AAV with increased BCR signaling, altered proportions of CD51 B cells, and decreased Breg numbers or function (105)(106)(107)171). Not surprisingly, therefore, rituximab in combination with corticosteroids is an effective (and Food and Drug Administrationapproved) therapy for inducing remission in patients with AAV, but its efficacy in treating patients with advanced renal disease has not been established yet (172).…”
Section: Role In Gnmentioning
confidence: 75%
“…Bregs have also been identified in humans, specifically in the CD24 high CD38 high transitional and CD24 high CD27 1 memory B-cell subsets, and their numbers correlate with better renal transplant outcomes (102)(103)(104). Altered numbers and/ or function of Bregs have been described in SLE and AAV, contributing to disease pathogenesis and/or relapse (102,(105)(106)(107). The presence of potent Bregs could explain why pan-depletion of B cells in humans using anti-CD20 (rituximab) has led to paradoxical or unsatisfactory clinical results in renal transplantation, as well as autoimmune renal disease (108,109).…”
Section: Bregsmentioning
confidence: 99%
“…There must also be additional investigation into determining predictive markers for individuals who need fixed versus intermittent dosing. It seems that higher relative percentages of peripheral regulatory B cells at the time of B-cell repopulation after rituximab may be associated with more prolonged remission (20,21). This finding could imply an increased risk of relapse at the time of rituximab cessation.…”
Section: Discussionmentioning
confidence: 99%
“…Bunch et al (43) have observed that the percentage of peripheral blood CD5-positive regulatory B cells is a useful indicator of disease activity, remission, and future relapse after rituximab therapy, and thus may help measure the effectiveness of induction therapy and guide maintenance therapy vigilance for relapse. To our knowledge, assays for CD5-positive B cells are not routinely available in clinical laboratories, although this test could be added to current flow cytometry lymphocyte phenotyping assays as a locally validated laboratory-developed test.…”
Section: Induction Of Remissionmentioning
confidence: 99%